MODERN DIRECTED ANTIVIRAL COVID-19 THERAPY: RESULTS OF MULTICENTER CLINICAL EFFECTIVENESS AND SAFETY STUDY OF FIXED NIRMATRELVIR+RITONAVIR COMBINATION - L. A. Balykova; N. M. Selezneva; E. I. Gorshenina; O. I. Shepeleva; N. V. Kirichenko; E. N. Simakina; K. B. Kolontarev; D. Yu. Pushkar; D. N. Zemskov; K. Ya. Zaslavskaya; S. M. Noskov; A. V. Taganov; et al. (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2022)
The article presents the data from an open, two-stage, multicenter study on the efficacy and safety evaluation of a combined drug (a fixed combination of nirmatrelvir 300 mg and ritonavir 100 mg) in the complex therapy in COVID-19 patients.The aim of the study was to assess the safety, tolerability and pharmacokinetic parameters of the fixed combination of nirmatrelvir 300 mg and ritonavir 100 mg in healthy volunteers, the efficacy and safety assessment of the drug in the combination therapy compared with the standard therapy in COVID-19 patients.Material and methods. An open two-stage multicenter clinical study to assess the main pharmacokinetic parameters, safety, and efficacy against COVID-19 of the drug nirmatrelvir 300 mg and ritonavir 100 mg combination (Skyvira® PROMOMED RUS LLC, Russia) in the adult population, included 2 stages. At stage 1, safety, tolerability and pharmacokinetic parameters were evaluated in healthy volunteers (over 18 years of age) in order to confirm their comparability with the literature data known for a set of active substances. Phase 2 assessed efficacy and safety in COVID-19 patients. As a part of the second stage, the study involved 264 patients (men and women aged 18 to 80 years), who had been divided into two groups. The first group patients (n=132) received the study drugs (nirmatrelvir 300 mg and ritonavir 100 mg) - 1 tablet twice a day with an interval of 12±2 hours for 5 days in combination with pathogenetic and symptomatic therapy. The second group patients (n=132) received standard therapy in accordance with the approved Temporary Guidelines for the Prevention and Treatment of Novel Coronavirus Infection (Version 15 dated February 22, 2022).Results. During the study, none of the patients from the (nirmatrelvir + ritonavir) group experienced a transition of the COVID-19 course to a heavier severity level, in contrast to the patients in the standard therapy group. The study participants included patients with comorbidities (68% of the general population), with risk factors for COVID-19 progression to a heavier severity level and the risk of hospitalization (75% of the general population). There were no cases of COVID-19 progression to a heavier severity level in the study drug group. By the 6th day, in the nirmatrelvir + ritonavir group, the proportion of the patients who had achieved a complete recovery was twice more and amounted to 35.61% (p=0.0001), and the proportion of the patients with a negative RNA analysis to SARS-CoV-2 was 20% higher than in the comparison group, and amounted to 82.58% (p=0.0001). The fixed nirmatrelvir + ritonavir combination therapy has a favorable safety profile comparable to the standard therapy. The identified adverse reactions were transient in nature and did not require discontinuation of therapy or changes in the treatment regimen.Conclusion. The fixed nirmatrelvir + ritonavir combination has a favorable safety profile in COVID-19 patients, comparable to the standard therapy. The data obtained demonstrate a clinical and pharmacoeconomic feasibility of including the fixed (nirmatrelvir + ritonavir) combination in the COVID-19 treatment regimen.